Odpowiedzi

2010-03-05T08:56:31+01:00
A) 2/5(3-x)=-2
6/5-2/5x=-2
-2/5x=-2-6/5
-2/5x=-16/5
x=-16/5*(-5/2)
x=8

b)1/5(x-3)=9-x
1/5x-3/5=9-x
1/5x+x=9+3/5
6/5x=48/5
x=48/5*5/6
x=8
1 5 1
2010-03-05T09:06:14+01:00
2/5(3-x)=-2
2/5*3-2/5x=-2
6/5-2/5x=-2
-2/5x=-2-6/5
-2/5x=-2-1,2
-2/5x=-3,2|*(-1)
2/5x=3,2
x=3,2:2/5
x=3,2:0,4
x=8


1/5(x-3)=9-x
1/5x-3/5=9-x
1/5x+x=9+3/5
6/5x=9+0,6
1,2x=9,6
x=8
1 5 1
2010-03-05T09:19:14+01:00
A) 2/5(3-x)=-2
6/5-2/5x=-2 /*5
6-2x=-10
-2x=-10-6
-2x=-16 /:(-2)
x=8

b)1/5(x-3)=9-x
1/5x-3/5=9-x /*5
x-3=45-5x
x=5x=45+3
6x=48 /:6
x=8
1 5 1